The visual symbolism of the matriarchal-kibelichnyh images in mythological representations of gender culture - I. O. Svyatnenko (Granì, 2016)
The article is devoted to the relationship between gender practices sociopathic culture matriarchal symbolism and visual-kibelical images of mythological and folk stories of different ethnic cultures. The author made conclusions that gender culture in matriarchal mythological folklore plots are typical following features. First, sacred motherhood, giving the image of the mother magical, fastsinalnymy, god-like attributes. The downside glorification of female victimization and acts mahizmu skotomizatsiya cholovitstva, fixing the men naive images of the victims, losers, artists routine cases and blind puppets female whims. Second, the gender culture matriarchy and kibelical manifestations of womanhood reflected tanatical motives kastratsiyni and uzalezhnyuyuchi treatment on male models who have to legitimize their status lower compared with women beings. Since any miflolohichnyy story, in the sense of the author, serves projection unconscious social representations and ekspektations of gender culture, then, subject to the application of the empirical method of research as depth unstructured interview «yu, unable to empirical data confirming of totality selected characteristics of gender culture matriarchy, not only in the past but in the present Ukrainian society. The parallelyty of women value judgments women to men their attrybution by chthonic traits in parallel accentation their own theomorphism says that myth and folklore does not act just the product of the imagination and allows point scenarios gender culture that often played in implicit form of social morality,